1977
DOI: 10.1021/j100520a012
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-induced polarization phenomena in the excited state of composite systems with identical halves. 2. Effects of solvent polarity upon the fluorescence of [2.2](1,3)pyrenophane

Abstract: The fluorescence spectrum as well as the absorption spectrum of [2.2] (1,3)pyrenophane (metapyrenophane) in nonpolar solvents such as methylcyclohexane are rather similar to those of pyrene. In polar solvents, metapyrenophane showed a broad structureless fluorescence band with maximum at 475 nm along with pyrene monomer-like emission at shorter wavelengths. The experimental results reported here suggest that the shorter wavelength fluorescence is from the locally excited (LE) state of metapyrenophane and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…A similar discussion has been given for the excimers of [2,2] (l,3)pyrenophane in polar and nonpolar solvents. 19 Brittain et al reported the CPF spectrum of the excimer of optically active l-(l-hydroxyhexyl)pyrene in methanol. 20 They found a decrease of the magnitude of gem below Xem = 460 nm and interpreted the decrease as the presence of more than one emitting species.…”
Section: Resultsmentioning
confidence: 99%
“…A similar discussion has been given for the excimers of [2,2] (l,3)pyrenophane in polar and nonpolar solvents. 19 Brittain et al reported the CPF spectrum of the excimer of optically active l-(l-hydroxyhexyl)pyrene in methanol. 20 They found a decrease of the magnitude of gem below Xem = 460 nm and interpreted the decrease as the presence of more than one emitting species.…”
Section: Resultsmentioning
confidence: 99%
“…73 A marked solvent-dependence is displayed by the emission of [2.2](l,3)pyrenophane. 69 In nonpolar solvents, such as methylcyclohexane the fluorescence originates entirely from locally excited pyrene at all temperatures. In polar solvents, such as acetonitrile and acetone, an intense excimer emission centered at 475 nm is observed in addition to pyrene monomer emission.…”
Section: B Pyrene In Glassy Matricesmentioning
confidence: 99%
“…The absorption spectra of the (1,3)pyrenophanes 7-10 are similar to that of pyrene, although the bands are a little broader and somewhat red-shifted (20-30 nm). 25,26 Since very similar changes also occur upon simple substitution at the 1 and 3 positions, it was concluded that there is little interaction between the two π systems. More interesting is the effect of solvent polarity on the fluorescence spectrum of anti- [2.2](1,3)pyrenophane 10.…”
Section: Scheme 2 (13)pyrenophanes Obtained From Multilayered Metacymentioning
confidence: 99%